2020
DOI: 10.1021/acschembio.0c00456
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Decarboxylase Controls Oxidative Maturation of the Prenylated Flavin Mononucleotide Cofactor

Abstract: Prenylated flavin mononucleotide (prFMN) is a recently discovered modified flavin cofactor containing an additional nonaromatic ring, connected to the N5 and C6 atoms. This cofactor underpins reversible decarboxylation catalyzed by members of the widespread UbiD enzyme family and is produced by the flavin prenyltransferase UbiX. Oxidative maturation of the UbiX product prFMNH2 to the corresponding oxidized prFMNiminium is required for ferulic acid decarboxylase (Fdc1; a UbiD-type enzyme) activity. However, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Studies on the maturation of prFMN in FDC, the best understood system, found that incubating the enzyme with oxidized prFMN actually led to loss of activity. 34 Also, an inverse relationship was observed between the amount of oxidized prFMN present in the reconstitution reaction and the final activity of the reconstituted FDC. These observations are in accord with our observation that to efficiently reconstitute PhdA, it was necessary to remove inhibitory prFMN species prior to oxidation.…”
Section: ■ Discussionmentioning
confidence: 94%
“…Studies on the maturation of prFMN in FDC, the best understood system, found that incubating the enzyme with oxidized prFMN actually led to loss of activity. 34 Also, an inverse relationship was observed between the amount of oxidized prFMN present in the reconstitution reaction and the final activity of the reconstituted FDC. These observations are in accord with our observation that to efficiently reconstitute PhdA, it was necessary to remove inhibitory prFMN species prior to oxidation.…”
Section: ■ Discussionmentioning
confidence: 94%
“…The versatility and evolvability of prFMN‐dependent fungal ferulic acid decarboxylases (FDCs) provide an opportunity to expand the synthetic scope of biocatalytic carboxylation reactions, for example towards functionalization of nonactivated aromatic compounds. Significant insights into prFMN [39,70,71,110,111] and FDC biochemistry [30,112] and (de)carboxylation substrate scope [41] supported development of FDC‐based carboxylation routes to enable access to industrially prevalent carboxylate derivatives including aldehyde, alcohols, amides and amines from simple nonactivated aromatic compounds by biocatalytic CO 2 ‐fixation cascades [43] . To address the severe equilibrium limitation encountered with the one‐step FDC‐catalyzed carboxylation reaction, the FDC‐mediated CO 2 fixation [43] was linked to carboxylate reduction, the latter step catalyzed by carboxylic acid reductases (CARs) [113–115] .…”
Section: Biocatalytic Co2‐fixation Cascades For Preparation Of Carboxmentioning
confidence: 99%
“…As such, needing both fdc1 and pad1 genes for the desired decarboxylase activity 18 , initially FDC has been studied in S. cerevisiae cultures, while later it has been shown that E. coli cultures expressing only the fdc1 gene, due to the presence of UbiX of the host E. coli cells, can also function as whole-cell biocatalysts with the desired FDC-activity 7 , 17 20 . Supposedly, the cofactor’s active iminium form is obtained inside FDC’s active site under the influence of oxygen 21 and a number of conserved residues 22 . However, in solution, prFMNH 2 can be irreversibly converted to inactive forms, such as prFMN C 4a -OOH 21 , prFMN-OH, prFMN radical , prFMN radical -H, prFMN iminium -OH, C 1 -ene-prFMN iminium 1 , 13 , 23 , 24 , while light decomposure has been also reported 22 , all these hindering the isolation of the holo-FDC.…”
Section: Introductionmentioning
confidence: 99%
“…Supposedly, the cofactor’s active iminium form is obtained inside FDC’s active site under the influence of oxygen 21 and a number of conserved residues 22 . However, in solution, prFMNH 2 can be irreversibly converted to inactive forms, such as prFMN C 4a -OOH 21 , prFMN-OH, prFMN radical , prFMN radical -H, prFMN iminium -OH, C 1 -ene-prFMN iminium 1 , 13 , 23 , 24 , while light decomposure has been also reported 22 , all these hindering the isolation of the holo-FDC.…”
Section: Introductionmentioning
confidence: 99%